Sex hormone receptors in varicose veins of women with premenstrual syndrome - Krasiński, Z.; Dzieciuchowicz, L.; Kotwicka, M.; Gabriel, M.; Szczęśniak-Chmielecka, A.; Krasińska, B.; Oszkinis, G.; Majewski, W. (Phlebologie, 2008)
The pathogenesis of premenstrual tension syndrome is not fully understood. It has been hypothesized that the interaction between sex hormones and target organs is the key event in its pathogenesis. Aim: The purpose of the study was to examine the differences in the prevalence of smooth muscle cells with sex hormones receptors in varicose veins of women with and without premenstrual tension syndrome (PS). Patients, methods: Samples of great saphenous vein were obtained from 50 women during varicose vein surgery. They were divided into group I (20 women with clinically diagnosed PS) and group II (30 women without PS). Estrogen and progesterone receptors were detected with an immunohistochemical method. Superficial densities of smooth muscle cells positive to estrogen and progesterone receptors were analyzed with densitometric program IM-AN and automatic image analyzer Magicall. The results were compared with t-Student test. Results: There were no differences in superficial density of smooth muscle cells positive to estrogen receptors between the groups. In contradiction to this, superficial density of smooth muscle cells positive to progesterone receptors was higher in group with PS than in patients without, 343 (±171) and 240 (±123), respectively. The difference was statistically significant (p < 0.05). Conclusion: The amount of cells with sex hormone receptors, not the level of hormones, could play a role in PS pathology. Our results show that progesterone is more important than estrogen in effector organs.
Keywords: Sex hormones; varicose veins; premenstrual tension syndrome